Developmental differences in relations between episodic memory and hippocampal subregion volume during early childhood - Riggins, Tracy (Child Dev, 2015)
Episodic memory shows striking improvement during early childhood. However, neural contributions to these behavioral changes are not well understood. The present study examined associations between episodic memory and volume of subregions (head, body, tail) of the hippocampus—a structure known to support episodic memory in school-aged children and adults—during early childhood (n=45). Results revealed significant positive relations between episodic memory and volume of the hippocampal head in both the left and right hemispheres for 6- but not 4-year-old children, suggesting brain-behavior relations vary across development. These findings add new information regarding neural mechanisms of change in memory development during early childhood and suggest developmental differences in hippocampal subregions may contribute to age-related differences in episodic memory ability.